KONSTRUKSI SOSIAL TATA RUANG PESANTREN AL-MUAYYAD MANGKUYUDAN SURAKARTA - Yusdiani, Yusdiani; Samroni, Imam (P3M STAIN Jurai Siwo Metro, 2013)
The following article denotes the result of research. The research is starting from the questionÂ how the process of the social production of spatial in Al-Muayyad boarding school? and how the meaning of spatial in Al-Muayyad boarding school? This study of the spatial interaction as the symbol used by the boarding school to signify a social relationship. This research is a qualitative and using phenomenological approach to the steps and stages of data reduction, data presentation, and conclusion / verification as an intertwined in the time before, during, and after the collection of data in parallel. The results of this study indicate there are two underlying spatial processes of social production Pesantren Al-Muayyad, the domination of religious clerics and social change towards development. In addition, the discourse on space in Al-Muayyad boarding school in addition to the function also represents a meaning. Utilization of space in this boarding schools distinguished by sacred and profane space. In addition to these meanings also have economic meanings.Keywords: konstruksi sosial, tata ruang, Al-Muayyad, makna dan semiotik